Biomimetic polysaccharide-cloaked lipidic nanovesicles/microassemblies for improving the enzymatic activity and prolonging the action time for hyperuricemia treatment. Issue 28 (8th July 2020) - Yang, Lan; Zhang, Yonghong; Xie, Jiangchuan; Zhong, Cailing; He, Dan; Wang, Tingting; Li, Kailing; Li, Yao; Shi, Da; Abagyan, Ruben; Yang, Lin; Zhang, Jingqing
Abstract : We prepare biomimetic polysaccharide hyaluronan-cloaked lipidic nanovesicles/microassemblies by entrapping uricase in the core of the hollow vesicles or by tethering them to the surfaces and then perform an antihyperuricemia evaluation of them. Abstract : The improvement and maintenance of enzymatic activities represent major challenges. However, to address these we developed novel biomimetic polysaccharide hyaluronan (Hn)-cloaked lipidic nanovesicles (BHLN) and microassemblies (BHLNM) as enzyme carriers that function by entrapping enzymes in the core or by tethering them to the inner/outer surfaces via covalent interactions. The effectiveness of these enzyme carriers was demonstrated through an evaluation of the enzymatic activity and anti-hyperuricemia bioactivity of urate oxidase (also called uricase, Uase). We showed that Uase was effectively loaded within the BHLN/BHLNM (UHLN/UHLNM) and maintained good enzymatic bioactivity through a range of effects, including isolation from the external environment due to the vesicle-carrying (shielding effect), avoidance of recognition by the reticuloendothelial system due to Hn-cloaking (long-term effect), production of beneficial conformational changes (allosteric effect) due to a favorable internal microenvironment of construction and vesicle loading, and stabilization due to the reversible conjugation of Uase or vesicle and serum albumin (deposit effect). UHLN/UHLNM had significantly increased bioavailability (∼533% and ∼331% compared to Uase) and demonstrated greatly improved efficacy, whereby the time required for UHLN/UHLNM to lower the plasma uric acid concentration to a normal level was much shorter than that for free Uase. The interactions of the therapeutic enzyme (Uase), biomimetic membrane components (Hn and phospholipid), and serum albumin were investigated with a fluorescent probe and computational simulations to help understand the superior properties of UHLN/UHLNM.